Assessment of Knowledge and Awareness Among the Stakeholders of Clinical Research at the Site: A Collaborative, Electronic-Survey Approach to Identify the Indicators of Quality - Pal, Chandana; Rengan, Aravind K.; Moodahadu, Latha; Swaminathan, Jayanthi; Nagalla, Balakrishna (Reviews on Recent Clinical Trials, 2023)
Background: There has been a concern about the quality of clinical trials conducted in terms of data integrity, accuracy or ethical conduct. This study aimed to assess the tangible gap existing in knowledge and application of rules and guidelines among the Researcher, Research staff (RS) and Ethics Committee (EC) members - the three research stakeholders at the study sites. Methods: A validated e-questionnaire with details for demography, role, years of experience, affiliation and questions on knowledge and understanding about their clinical research functions based on the New Drugs and Clinical Trials (NDCT) Rules 2019, including: ‘Role and responsibility, Regulations, Reporting timelines, Documentation, Conflict of interest and Miscellaneous’ was circulated among the seven research sites of one organization with their fourteen Institutional ECs, as part of planned annual survey. Responses with >60% correct answers were arbitrarily considered to represent adequate knowledge. Results: Of 201 participants, there were 27.4% Researchers, 50.2% were from the EC and 22.4% RS. A greater proportion of the Researchers (43.6%) had >5 years of experience. The mean ± SD of correct answers obtained was 66.9 ± 14.77 and was statistically significant (p<0.05) among the groups, highest for the EC members (71.4 ± 11.51), those with 2-5 years of experience (68.4 ± 14.40), and least for the RS (56.8 ± 11.93). Researchers (> 90%) were aware of their role in the clinical trial agreement and the importance of the trial registration in the Clinical Trials Registry India. There were gaps in the knowledge on Informed Consent (IC) process and post-trial access. Awareness regarding the IC process was adequate among the RS (84%). Awareness that the responsibility of all delegation at the site finally lies with the Researchers was adequate (60%), but 20% incorrectly believed that the sponsor can have access to subject identification details. Deficiencies were noted regarding documentation, NDCT rules -2019 and serious adverse event (SAE) reporting process. Five percent answered that Data Clarification Forms were generated after reviewing the case report forms. The awareness that NDCT rules-2019 was not for medical devices, student projects or Investigator Initiated Studies was inadequate (56%). The EC members’ awareness of roles and responsibilities was adequate (≥ 90%). Knowledge gaps were noted in EC monitoring of the ongoing trials (32%) and SAE reporting on the SUGAM portal (8.8%), where stakeholders can access the regulator's web services using a single window interface for clinical trial related activities. Conclusion: There are gaps in the knowledge of the 3 stakeholders at the site. Identifying and rectifying the gray areas will improve the site's performance. There is a need for regular training and assessments.
Keywords: SUGAM portal